“Survival” of Older Persons in the Labour Market: the Case of Lithuania in the EU Context - Navickė, Jekaterina; Straševičiūtė, Žeimantė (Socialinė teorija, empirija, politika ir praktika, 2023)
The rapidly ageing populations are a source of concern, but they also provide new opportunities. The purpose of this article is to analyse the factors which affect the participation of older persons in the Lithuanian labour market. The research method is based on data from SHARE (7-8 waves). The research shows that the factors of participation of older persons in the Lithuanian labour market can be mainly linked to the group of involuntary "stuck" factors. Older persons in Lithuania mostly want to leave the labour market as soon as possible. Retaining older persons in the labour market often depends on financial motives. The main challenges for employment in old age are related to the reduction of involuntary motives and to the promotion of positive voluntary motives to stay in the labour market.